Exploring multidimensional aspects of walkability: An innovative analysis approach in Besiktas, Istanbul - Yildirim, Ozge Ceylin; Sungur, Asli; Ozer, Derya Gulec (KEAI PUBLISHING LTD, 2023)
This study develops a holistic approach that underlines the effect of spatial, behavioral, and perceptional dimensions on walkability at the neighborhood scale. The study recognizes quantitatively measured tangible factors and qualitatively assessed intangible values to evaluate the level of walkability in Besiktas, Istanbul (Turkey). The research explores the independent and combined effects of physical characteristics, individual perceptions, and walking behavior on walkability. Geographic Information Systems urban analyses, space syntax analysis, and observation to establish an analytical framework for spatial and behavioral dimensions of walkability in Besiktas central district are used as a methodology. Additionally, perceptional data is gathered through an experimental approach, which involves participants walking along pre-determined routes using cartography techniques and employing shared walks as a mobile method. The results of study confirmed previous findings from studies that the physical, social, and typological attributes of the built environment have a significant correlation between walking behavior and the physical and social aspects of the built environment. This study provides a comprehensive walkability assessment framework, encompassing quantitative and qualitative dimensions. By incorporating spatial, behavioral, and perceptual dimensions, this approach provides an efficient and integrated analytical methodology for evaluating walkability, distinguishing itself with its originality in the field of walkability research. (c) 2023 Higher Education Press Limited Company. Publishing services by Elsevier B.V. on behalf of KeAi Communications Co. Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Walkability; Mixed methods; Space syntax; Mobile methodologies; Critical cartography; VOLUNTEERED GEOGRAPHIC INFORMATION; DESIGNING HEALTHY COMMUNITIES; NEIGHBORHOOD WALKABILITY; PEDESTRIAN BEHAVIOR; PHYSICAL-ACTIVITY; ACTIVE-TRANSPORT; WALKING; URBAN; PERCEPTIONS; ENVIRONMENT; Architecture